Study of the catalytical intermediates of metalloporphyrins supported on imidazole propyl gel - Iamamoto, Y.; Prado, CMC; Sacco, H. C.; Ciuffi, K. J.; Assis, M. D.; Maestrin, APJ; Melo, AJB; Baffa, O.; Nascimento, O. R. (Elsevier B.V., 1997)
In this work, the catalytic intermediates for Fe(TPP)(+), Fe(TDCPP)(+), Fe(TFPP)(+), Mn(TPP)(+) and Mn(TDCPP)(+) supported on imidazole propyl gel with PhIO were studied by UV-Vis spectrophotometry. For Fe(TPP)+ and Fe(TFPP)+ the study was also monitored by EPR spectroscopy. The active catalytic intermediate observed for FeP-IPG is the ore-iron (IV) porphyrin pi cation radical Fe-IV(O)P.+, which is evidenced by a decrease in the intensity of the Sorer band. The total re-establishment of the initial Soret band intensity for Fe(TDCPP)IPG and Fe(TFPP)IPG at the end of the reaction shows that they were completely recovered, There are advantages in following the reactions of PNO with unsubstituted Fe(TPP)(+) and Mn(TPP)(+) on IPG by UV-Vis, since they were slower and allowed to 'see' the intermediate species without spectral interference from the recovered catalyst, since they are only partially recovered. With Fe(TPP)IPG, a band at 580 nm was detected at the beginning of the reaction, indicating the possible formation of a Fe-OIPh intermediate. Supporting Mn(TPP)(+) on IPG leads to a shift of band V from 478 nm to 488 nm. In the reaction of MnP-IPG with PhIO, we observed the disappearance of the band in 488 nm and the appearance of a band in 412 nm, which corresponds to the active catalytic intermediate Mn-V(O)P as the main component, as is expected for a more efficient system. The recovery of supported catalysts observed in these experiments was further proved with the possibility of their successive recyclings in cyclohexane oxidation reactions by PhIO.
Keywords: porphyrins; metalloporphyrins; supported intermediates; intermediates; imidazole propyl gel